Quem são os sujeitos que habitam a planície fluvial do Rio Jaguari no município de Jaguari/RS? - Mello, Isabela Silveira (2020)
Floods are extreme precipitation events, so the riverside regions of the floodplains are prone to the impacts of major river floods. In the state of Rio Grande do Sul there are several cities that have a significant population residing on the banks of the rivers. In Jaguari, in the central region of the state, this phenomenon occurs at least once a year, where the river that names the city spills into its bed and its tributaries, forcing many families to leave their homes. As it is a small city with approximately 11 thousand inhabitants, flooding episodes recur and directly impact the lives of the people who live there. Most of the population affected by the floods of the Jaguari River, are inserted in low-income housing units and carry with them some indignation regarding the actions of the competent agencies. This research aimed to characterize and discuss who are the subjects affected by flooding in the city of Jaguari/RS, whether they carried characteristics of riverside populations or not. Through the case study methodology and the application of semi-structured questionnaires together with the quantitative approach, it is possible to reach satisfactory results that provided subsidies to answer the guiding question that started the work. Finally, from the analysis of the results it can be concluded that this population is in fact able to live in a space of social and territorial segregation, where they are not assisted by the city, rarely receive help from them and, therefore, are not organized in function of claiming improvements for its territory.